Effects of Polyethylene Glycol‐20k on Coronary Perfusion Pressure and Postresuscitation Myocardial and Cerebral Function in a Rat Model of Cardiac Arrest. Issue 3 (4th February 2020) - Ge, Weiwei; Zheng, Guanghui; Ji, Xianfei; He, Fenglian; Hu, Juntao; Bradley, Jennifer L.; Moore, Christine E.; Peberdy, Mary A.; Ornato, Joseph P.; Mangino, Martin J.; Tang, Wanchun
Abstract : Background: Epinephrine increases the rate of return of spontaneous circulation. However, it increases severity of postresuscitation myocardial and cerebral dysfunction and reduces duration of survival. We investigated the effects of aortic infused polyethylene glycol, 20 000 molecular weight (PEG‐20k) during cardiopulmonary resuscitation on coronary perfusion pressure, postresuscitation myocardial and cerebral function, and duration of survival in a rat model of cardiac arrest. Methods and Results: Twenty‐four male rats were randomized into 4 groups: (1) PEG‐20k, (2) epinephrine, (3) saline control–intravenous, and (4) saline control–intra‐aortic. Cardiopulmonary resuscitation was initiated after 6 minutes of untreated ventricular fibrillation. In PEG‐20k and Saline‐A, either PEG‐20k (10% weight/volume in 10% estimated blood volume infused over 3 minutes) or saline was administered intra‐aortically after 4 minutes of precordial compression. In epinephrine and placebo groups, either epinephrine (20 μg/kg) or saline placebo was administered intravenously after 4 minutes of precordial compression. Resuscitation was attempted after 8 minutes of cardiopulmonary resuscitation. Sublingual microcirculation was measured at baseline and 1, 3, and 5 hours after return of spontaneous circulation. Myocardial function was measured at baseline and 2, 4, and 6 hours after return of spontaneous circulation. Neurologic deficit scores were recorded at 24, 48, and 72 hours after return of spontaneous circulation. Aortic infusion of PEG‐20k increased coronary perfusion pressure to the same extent as epinephrine. Postresuscitation sublingual microcirculation, myocardial and cerebral function, and duration of survival were improved in PEG‐20k ( P <0.05) compared with epinephrine ( P <0.05). Conclusions: Aortic infusion of PEG‐20k during cardiopulmonary resuscitation increases coronary perfusion pressure to the same extent as epinephrine, improves postresuscitation myocardial and cerebral function, and increases duration of survival in a rat model of cardiac arrest.